Free falling - Shalvis, Jill (Colburn brothers, 2026)
"First, they were rivals... Now they're stuck with each other... Retired hockey player Caleb Colburn needs this construction project to prove himself in the family business, but he also needs to recover from the injury that ended his pro career. Too bad Emma Sumner, architect liaison and Caleb's college nemesis, is back in town and assigned to the project. They're going to have to see each other almost every day. Which means once again she'll make his life a living hell. As for Emma, her job is on the line with this big project, made all the more challenging by the project manager. Caleb was the one who had snagged the scholarship she'd desperately needed to stay in college. She's been living hand to mouth ever since and has no intention of ever forgiving the man. But the beautiful historic building they're renovating is exactly the kind of project that they both love best. Their surprising common ground and a burning mutual attraction start bringing them closer and closer to a potentially explosive mistake. And that's even before the secrets come out"-- Provided by publisher.